PENGARUH LIKUIDITAS, LEVERAGE, DAN PROFITABILITAS TERHADAP RETURN SAHAM PT. AGUNG PODOMORO LAND, TBK - Ida Yusnita; Tiara Lilis Surya (LP2M Universitas Bina Bangsa, 2024)
This study aims to: 1. To determine the effect of Liquidity on Stock Returns at PT. Agung Podomoro Land, Tbk in 2012 – 2020. 2. To determine the effect of leverage on stock returns at PT. Agung Podomoro Land, Tbk in 2012 – 2020. 3. To determine the effect of Profitability on Stock Returns at PT. Agung Podomoro Land, Tbk 2012 – 2020. 4. To determine the effect of Liquidity, Leverage and Profitability on Stock Returns at PT. Agung Podomoro Land, Tbk simultaneously in 2012 – 2020. 5. To find out the influence of Liquidity, Leverage and Profitability on PT. Agung Podomoro Land, Tbk 2012 – 2020. The research methodology used is a qualitative descriptive and quantitative descriptive approach. Research results namely; 1. Partially there is no effect of CR on stock returns of PT. Agung Podomoro Land, Tbk in 2012 – 2021 as evidenced by the tcount <ttable (1.629 <2.44691) 2. Partially there is no effect of DAR on PT. Agung Podomoro Land, Tbk in 2012 – 2021 as evidenced by the value -tcount > -ttable (-0.046 > -2.44691) 3. Partially there is no effect of ROA on PT. Agung Podomoro Land, Tbk in 2012 – 2021 as evidenced by the value of tcount <ttable (0.760 <2.44691) 4. Simultaneously there is no effect of CR, DAR and ROA on PT. Agung Podomoro Land, Tbk in 2012 – 2021 as evidenced by the value of fcount <ftable (0.983 <4.76) 5. The magnitude of the influence of CR, DAR and ROA on PT. Agung Podomoro Land, Tbk in 2012 – 2021 is 33%